The Influence of Numerical literacy on Students’ Mathematical Problem-Solving Ability - Danial Danial; Kalfin Kalfin; Husnul Muawiyah (Research Collaboration Community (Rescollacom), 2026)
This study aims to determine the influence of numerical literacy on the improvement of mathematical problem-solving ability among Grade VIII students at State Junior High School of 13 Sinjai. This research employed an ex post facto design with a quantitative approach. The population of this study consisted of all Grade VIII students at State Junior High School of 13 Sinjai, totaling 57 students, with a saturated sampling technique. Data analysis was conducted using simple linear regression to examine the influence of numerical literacy on students’ mathematical problem-solving ability. The results showed that the significance value was 0.000 < 0.05 and the calculated t-value was 18.24, which was greater than the t-table value of 2.101, indicating a significant effect between numerical literacy and students’ mathematical problem-solving ability. In addition, the coefficient of determination (R Square) value of 0.948 indicates that numerical literacy contributes 94.8% to the improvement of students’ mathematical problem-solving ability, while the remaining percentage is influenced by other factors outside this study